Facile synthesis of lithium argyrodite Li5.5PS4.5Br1.5 with high ionic conductivity for all-solid-state batteries - Wang, Shuo; Wu, Xinbin; Liang, Yuhan; Xu, Yushuai; Guan, Shundong; Wen, Kaihua; Miao, Xiang; Liang, Ying; He, Hongcai; Lin, Yuanhua; Shen, Yang; Nan, Ce-Wen (Frontiers in Chemical Engineering, 2022)
Bromine-rich lithium argyrodite electrolytes with high ionic conductivity and low cost merit are promising for replacing the flammable liquid electrolytes and separators in lithium-ion batteries. However, the synthesis process of the argyrodite electrolytes is usually complex and time-consuming. Herein, we use a facile solid-state reaction method to obtain a highly Li-ion conductive Li5.5PS4.5Br1.5 (LPSB). The influence of annealing temperature on the phase and ionic conductivity of the LPSB is investigated for the first time. A high ionic conductivity of 5.21×10-3 S cm-1 at room temperature for the LPSB with minor LiBr impurity is achieved by directly annealing at 430C for 8 h. The In/InLi | LPSB | LiCoO2@ LiNb0.5Ta0.5O3 (LCO(coated))-LPSB cell with 8.53 mg cm-2 LCO loading shows a discharge capacity of 102 mAh g-1 with a high capacity retention of 93% after 70 cycles at 0.5 mA cm-2 at 30°C.